FIRST DESCRIPTION OF ARGININE CATABOLIC MOVILE ELEMENT (ACME) TYPE VI HARBORING THE kdp OPERON ONLY IN Staphylococcus epidermidis USING SHORT AND LONG READ WHOLE GENOME SEQUENCING: FURTHER EVIDENCE OF ACME DIVERSITY - Coleman, David; Mc Manus, Brenda (My University, 2019)
The arginine catabolic mobile element (ACME) was first described in methicillin-resistant Staphylococcus aureus and is considered to enhance transmission, persistence and survival. Subsequently ACMEs were shown to be more prevalent in the coagulase-negative Staphylococcus epidermidis. Previously, ACME types were distinguished by characteristic combinations of the arc and opp3 operons [I (arc+, opp3+), II (arc+, opp3-) and III (arc-, opp3+)] encoding an arginine deaminase pathway and oligopeptide permease transporter, respectively. Recently two novel ACME types harboring the potassium transporter-encoding operon kdp were described in oral S. epidermidis isolates [IV (arc+, opp3-, kdp+), and V (arc+, opp3+, kdp+)]. This study investigated two independent oral S. epidermidis isolates that yielded amplimers with kdp-directed primers only when subjected to ACME typing PCRs. Hybrid assemblies based on Illumina MiSeq short-read and Oxford Nanopore MinION long-read whole genome sequences revealed that both isolates harbored a sixth, novel ACME type (VI) integrated into orfX. Both ACME VIs lacked the arc and opp3 operons, harbored the kdp operon adjacent to other commonly ACME-associated genes including speG, hsd, sdr, and rep, but the structural organization of the adjacent regions were distinct. These ACMEs were flanked by different direct repeat sequences and the ACME VI-positive isolates belonged to unrelated genetic clusters. Overall these findings are indicative of independent evolution. The identification of ACME type VI further illustrates the diversity of ACME elements in S. epidermidis. The presence of ACMEs harboring kdp may confer a selective advantage on oral S. epidermidis in a potassium-rich environment such as found in dental plaque.
PUBLISHED
18th March 2019; Epub ahead of print
Keywords: ACME; Staphylococcus epidermidis; kdp operon; Potassium uptake; Oral cavity; Immunology, Inflammation & Infection; ACME; ACME TYPE VI ELEMENT; Arginine catabolic mobile element; Hybrid genome assembly; ORAL STAPHYLOCOCCUS EPIDERMIDIS; Short and long read sequencing; Staphylococcus epidermidis; Whole Genome Sequencing; kdp operon